Pengaruh Pemberian Kompos TKKS dan Pupuk NPK Terhadap Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) - Haloho, Jonarti; Murniati, Murniati; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research was conducted at experimental farm, The Faculty of Agricultute, Riau University from March until July 2016 to look the effect of palm oil empty bunch compost and NPK fertilizer for corn growth and productivity and to know the best dosage. The research factorial 4x4 and three replication was arranged in Randomized Completely Block Design. The first factor was  palm oil empty bunch compost (without palm oil empty bunch compost, 5 ton/ha, 10 ton/ha, and 15 ton/ha) and the second factor was NPK fertilizer (without NPK fertilizer, 100 kg/ha, 200 kg/ha, and 300 kg/ha). From both factor there are 16 treatment combination which repeat three times. The result revelaed that palm oil empty bunch compost and NPK fertilizer combination significant effect with plant’s growth, the ration of roots crown, dry weight of plants, diameter of rod, diameter of cobs, length of cob, weight of seed, a thousand weight of seeds and not significant with total leaf area and height of plant’s . The combination of 5 ton/ha palm oil empty bunch compost and           200 kg/ha NPK fertilizer showed the best weight of seeds obtained was             4,85 kg/6 m2 than without palm oil empty bunch compost and NPK fertilizer that obtained was   3,70 kg/6 m2  weight of seeds. Keyword: TKKS compost, NPK fertilizer, Corn.